2014
DOI: 10.1115/1.4026294
|View full text |Cite
|
Sign up to set email alerts
|

A New Laparoscopic Morcellator Using an Actuated Wire Mesh and Bag

Abstract: Laparoscopic morcellation is a technique used in gynecological surgeries such as hysterectomy and myomectomy to remove uteri and uterine fibroids (leiomyomas) through a small abdominal incision. Current morcellators use blades or bipolar energy to cut tissue into small pieces that are then removed through laparoscopic ports in a piecewise manner. These existing approaches have several limitations; (1) they are time consuming as the tissue must be manually moved over the devices during the cutting step and remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…2 Laparoscopic morcellation is a technique used in gynecological surgeries such as hysterectomy and myomectomy to remove uteri and uterine fibroids (leiomyomas) through a small abdominal incision. 4 The morcellators are tiny devices with rotating blades that break large tissue masses into small fragments. 5 Tissue morcellation during gynecologic surgery has been widely practiced to facilitate removal of large uteri or uterine myomas through less invasive incisions than those used in a traditional laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Laparoscopic morcellation is a technique used in gynecological surgeries such as hysterectomy and myomectomy to remove uteri and uterine fibroids (leiomyomas) through a small abdominal incision. 4 The morcellators are tiny devices with rotating blades that break large tissue masses into small fragments. 5 Tissue morcellation during gynecologic surgery has been widely practiced to facilitate removal of large uteri or uterine myomas through less invasive incisions than those used in a traditional laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…74 Another recent report describes an enclosed, motor-actuated mesh that applies inward-directed cutting force to tissue that has been loaded into mesh within a protective bag. 75 This approach could be applied to a larger range in tissue size and density as compared with current power morcellators, while decreasing the risks of seeding and injury to other organs and structures. As contained power morcellation techniques gain approval for in vivo use, they likely will become the predominant approach with the advantages of decreased operative time while avoiding dissemination of endometriosis or malignancy and decreasing intraoperative injury as compared with current open morcellation techniques.…”
Section: Surgical Alternativesmentioning
confidence: 99%
“…Einarsson et al have reported on the technique of contained electromechanical or ‘in bag’ morcellation which may help avoid tissue dissemination and visceral injury, however further studies are needed [62]. New devices specifically aimed at contained mechanical morcellation are in development [66].…”
Section: Future Perspectivementioning
confidence: 99%